Exploring Leadership Practices and Proposed Leadership Development Program: Case Study at Indonesian Aviation Manufacturing Companies - Taufiqurrahman, Dafa; Gustomo, Aurik (Syntax Corporation, 2025)
National defense plays a crucial role in maintaining territorial integrity and the security of the nation against various threats. The dynamics of the strategic environment demand updates in human resource development in the defense sector to support sustainable national development. Leadership practices are essential for achieving organizational effectiveness, especially in strategic industries such as aviation manufacturing. This research aims to explore and evaluate leadership development practices in the aviation manufacturing industry using a qualitative approach. Primary and secondary data were collected through interviews with stakeholders involved in leadership development within the company. Data analysis was conducted using NVivo to identify themes and subthemes, as well as to perform coding and data categorization. The research findings reveal several challenges in program implementation, including a lack of measurable evaluation, inconsistencies in procedures, and suboptimal use of learning technologies. These weaknesses limit the organization’s ability to improve performance and long-term sustainability. Based on the analysis of the findings, opportunities for program development include establishing a measurable evaluation framework, developing a standardized framework, and implementing a holistic feedback mechanism. Additionally, upgrading the learning management system to cope with the digital age is a priority to maximize effective and efficient learning.